2014
DOI: 10.1371/journal.pone.0104266
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Strategies for Improving Patient Adherence to Follow-Up in the Era of Mobile Information Technology: A Systematic Review and Meta-Analysis

Abstract: BackgroundPatient adherence to follow-up plays a key role in the medical surveillance of chronic diseases and affects the implementation of clinical research by influencing cost and validity. We previously reported a randomized controlled trial (RCT) on short message service (SMS) reminders, which significantly improved follow-up adherence in pediatric cataract treatment.MethodsRCTs published in English that reported the impact of SMS or telephone reminders on increasing or decreasing the follow-up rate (FUR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Patients with glaucoma require lifelong treatment and follow-up care for preservation of vision 13. The importance of adherence to follow-up regimens is highlighted in several studies, all of which found an association between worsening glaucoma severity and poor follow-up 14 15.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with glaucoma require lifelong treatment and follow-up care for preservation of vision 13. The importance of adherence to follow-up regimens is highlighted in several studies, all of which found an association between worsening glaucoma severity and poor follow-up 14 15.…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant cost 16 associated with surgical interventions, the effort to obtain good-quality follow-up is minimal. [17][18][19] Summary What was known before K Initial work in Tanzania identified reasons for poor follow-up. K There is limited information on educational placement following sight-restoring or sight-improving surgery in children.…”
Section: Discussionmentioning
confidence: 99%
“…Although technology-based interventions targeting weight loss have been conducted previously [34], the use of technology in PCP-mediated interventions is rarely seen. Importantly, emerging work shows the promise for technology to facilitate follow-up and increase patient adherence to prescribed treatments and interventions [35]. Since provider time can be quite limited and thus costly to use for follow-up activities, future interventions could use technology services such as text/SMS (short message service) and/or automated telephone reminders for follow-up.…”
Section: Discussionmentioning
confidence: 99%